Pengaruh perputaran modal kerja piutang kas dan persediaanterhadapnet profit margin pada perusahaan industri barang konsumsi di BEI - Martius Martius (JURNAL PUNDI, 2018)
In the development of free trade and great globalization to the way the company in carrying out operational activities in order to be more effective and efficient. This study aims to determine the turnover of working capital, receivable turnover, cash turnover and inventory turnover of Net Profit Margin (NPM) in consumer goods industry companies listed on the Indonesia Stock Exchange period 2012-2016. The sampling technique used is purposive sampling with the criteria of Consumer Goods Industry which always present the financial statements as of December 2012-2016. The results of this study indicate that partially working capital turnover and receivable turnover have no significant effect on net profit margin, while receivable turnover and cash turnover and inventory turnover significantly influence net profit margin. But simultaneously rotation of working capital, receivable turnover, cash turnover and inventory turnover significantly affect net profit margin. The Adjusted R square value shows that secar jointly with working capital turnover, receivable turnover, cash turnover and inventory turnover contributed to net profit margin of 38.3% while the remaining 61.2% was influenced by other variables not included in this study.